2011
DOI: 10.1007/s10526-011-9387-1
|View full text |Cite
|
Sign up to set email alerts
|

Living with the enemy: parasites and pathogens of the ladybird Harmonia axyridis

Abstract: Harmonia axyridis is an invasive alien predator in many countries across the world. The rapid establishment and spread of this species is of concern because of the threat it poses to biodiversity as a generalist predator. Understanding the mechanisms that contribute to the success of this species as an invader is not only intriguing but also critical to our understanding of the processes governing such invasions. The enemy release hypothesis (ERH) could explain the rapid population growth of many invasive alie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 91 publications
0
55
0
Order By: Relevance
“…The association between Harmonia axyridis and Hesperomyces virescens is an example of the latter, less frequent, process. The case described above can be included with an increasing body of evidence that the invasive populations of the harlequin ladybird are not only susceptible to some native parasites such as H. virescens, the mite Coccipolipus hippodamiae (McDaniel & Morrill) (Rhule et al, 2010;Riddick, 2010) and allantonematid nematodes (Harding et al, 2011;Roy et al, 2011b;Poinar & Steenberg, 2012), but also contribute to their dispersal, increase in prevalence and intensity of infection.…”
Section: Newly Emergent Host-parasite Associationmentioning
confidence: 99%
“…The association between Harmonia axyridis and Hesperomyces virescens is an example of the latter, less frequent, process. The case described above can be included with an increasing body of evidence that the invasive populations of the harlequin ladybird are not only susceptible to some native parasites such as H. virescens, the mite Coccipolipus hippodamiae (McDaniel & Morrill) (Rhule et al, 2010;Riddick, 2010) and allantonematid nematodes (Harding et al, 2011;Roy et al, 2011b;Poinar & Steenberg, 2012), but also contribute to their dispersal, increase in prevalence and intensity of infection.…”
Section: Newly Emergent Host-parasite Associationmentioning
confidence: 99%
“…Roy et al [10] suggest that H. virescens is probably native to North America, referring to the fact that Thaxter [33] first found it in the USA on C. stigma and Hippodamia convergens Guérin-Méneville, 1842, both native to North America [34]; soon more recordings from new localities extended the distribution of H. virescens to South America, Asia, and Oceania [35,36]. The (historical) records for China of H. virescens parasitizing H. axyridis in this study give rise to the suggestion that H. virescens is a global species.…”
Section: Discussionmentioning
confidence: 99%
“…This combination between genetically diverse populations from the native range may have facilitated the success of H. axyridis in North America, and consequently its subsequent expansion. It has been suggested that with the rapid expansion of H. axyridis also H. virescens will continue to spread globally [10] and threaten native, noninvasive Asian populations of H. axyridis [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations